COVID-19 Vaccinations: Summary Guidance for Cancer Patients in 28 Languages: Breaking Barriers to Cancer Patient Information - Mauri, Davide; Kamposioras, Konstantinos; Tsali, Lampriani; Dambrosio, Mario; De Bari, Berardino; Hindi, Nadia; Salembier, Carl; Nixon, Joanna; Dimitrios, Tzachanis; Alongi, Flippo; Hameed, Hassan; Valachis, Antonios; et al. (Reviews on Recent Clinical Trials, 2022)
Background: Covid-19 vaccination has started in the majority of the countries at the global level. Cancer patients are at high risk for infection, serious illness, and death from COVID-19 and need vaccination guidance and support. Guidance availability in the English language only is a major limit for recommendations’ delivery and their application in the world’s population and generates information inequalities across the different populations. Methods: Most of the available COVID-19 vaccination guidance for cancer patients was screened and scrutinized by the European Cancer Patients Coalition (ECPC) and an international oncology panel of 52 physicians from 33 countries. Results: A summary guidance was developed and provided in 28 languages in order to reach more than 70 percent of the global population. Conclusion: Language barrier and e-guidance availability in the native language are the most important barriers when communicating with patients. E-guidance availability in various native languages should be considered a major priority by international medical and health organizations that are communicating with patients at the global level.
Keywords: vaccination